Analgesic efficacy of preoperative ultrasound-guided interscalene block versus intravenous morphine on postoperative pain relief after shoulder surgeries - Huda Fahmy (Wolters Kluwer Medknow Publications, 2019)
Background Postoperative pain relief is a major concern for the anesthesiologist after shoulder surgeries. Aim The aim of the study was to compare the efficacy of preoperative ultrasound-guided interscalene brachial plexus block (ISPB) and postoperative intravenous morphine for postoperative analgesia in shoulder surgeries. Patients and methods This prospective, randomized study was performed on 40 patients who were scheduled for different types of shoulder surgery under general anesthesia, with ASA physical status between I and II. The patients were divided equally and randomly into two groups to receive ISPB or intravenous morphine. Results Patient demographic characteristics, operative data, and ASA classification were similar between the groups. The mean pain score was significantly lower in ISPB compared with the intravenous morphine group at 3, 6, and 12 h postoperatively (P<0.05). Additionally, the ISPB group was associated with statistically significant lower morphine consumption (P<0.001) and the number of patients who required additional analgesia 3 h postoperatively was 3 (20%) versus 17 (75%) in the morphine group (P=0.000). Conclusion The present randomized trial shows that ultrasound-guided ISPB provides better postoperative analgesia and reduces the need for postoperative morphine than opioids alone among patients scheduled for open shoulder surgery.